A simple method for assaying anaerobic biodegradation of dyes. (March 2018) - Xiao, Xiang; Li, Ting-Ting; Lu, Xue-Rong; Feng, Xiao-Li; Han, Xue; Li, Wen-Wei; Li, Qian; Yu, Han-Qing
Graphical abstract: Highlights: A high-throughput system was established to assay anaerobic degradation of dyes. This simple, cost-effective approach was verified by anaerobic decolorization. Anaerobic dye degradation mechanism depended on their molecular polarities. This method is helpful for assaying anaerobic treatment of dye-rich wastewaters. Abstract: Anaerobic dye degradation is usually assayed using serum vials, which is time-consuming and costly. In this work, a simple method was established for real-time nondestructive assay of dye biodegradation using 96-well microtiter plates with petrolatum oil to avoid the volatilization and high transmittance transparent tape to prevent the permeation of oxygen. With the anaerobic degradation of methyl red and amaranth by Shewanella oneidensis MR-1, this assay method was verified. Further experiments revealed that blocking Mtr pathway had no substantial effect on the degradation of methyl red and dose of riboflavin also failed to promote the degradation of methyl red. On the contrary, the anaerobic degradation of amaranth depended mainly on the electron transmembrane transfer through Mtr pathway. Our work clearly indicates that Mtr pathway had different effects on intra- and extra-cellular degradation of azo dyes by S. oneidensis MR-1. Such a developed method is helpful for investigating anaerobic dye decolorization.